Pameran Bisnis Ibu-Ibu Desa Glagaharum sebagai Upaya Meningkatkan Pendapatan untuk Mencapai Sustainable Development Goals (SDGs) - Santoso, Brian Timothy; Lainardy, Jesslyn Eunice; Tjioe, Vincentia Jennifer Evelyn; Sitepu, Sri Nathasya Br (Universitas Nusantara PGRI Kediri, 2025)
Glagaharum Village is one of the villages in Porong District, Sidoarjo. Housewives of Glagaharum Village have high potential to improve their village's economy with their sewing skills. However, knowledge in calculating the cost of goods sold and marketing products effectively is still very minimal. Therefore, the